A Review of Foreign Language Enjoyment and Engagement - Zeng, Yijun (Frontiers in Psychology, 2021)
The introduction of positive psychology into foreign/second language learning has led to a multitude of novel theoretical and empirical studies. Foreign language enjoyment (FLE) is regarded as a response to the widely examined concept of classroom anxiety. The majority of these studies have investigated the effect of learners’ and teachers’ characteristics (Xie & Derakhshan, 2021) pertaining to FLE on learners’ academic achievement and their engagement in classroom tasks. Following a seminal study by Dewaele and MacIntyre (2014) and the development of the primary FLE scale, some researchers evaluated the extent of learners’ enjoyment in the language learning environment; these studies approved the effectiveness and prominence of FLE throughout the learning process. The present review is an attempt to review studies on FLE during the past two decades. The related literature confirms the significance and efficiency of promoting FLE in the classroom because it brings about higher levels of motivation and engagement among language learners and leads to prolonged success and achievement. A summary of the major efforts regarding this area of research is presented in this study.